Pengaruh Beban Kerja dalam Memediasi Pengaruh Penggunaan Rekam Medis dan Lingkungan Kerja terhadap Kinerja Dokter Gigi di Area Tangerang Selatan dan Tangerang Kota - Ferdianto, Antonius; Purnama, Desy; Tarumingkeng, Rudy C. (Universitas Batanghari Jambi, 2025)
The research aims to determine the influence of workload in mediating the influence of the use of medical records and the work environment on the performance of dentists in the South Tangerang and Tangerang City areas. The research method used is quantitative descriptive with a path model as the analysis. The number of respondents studied was 93 dentists. These results and analysis show that all indicators used in this research are valid and reliable. Furthermore, the use of medical records affects the performance of dentists. The work environment does not affect the dentist's performance. Medical records have no effect on workload. The work environment influences workload. Workload does not affect the performance of dentists. Workload mediates the effect of the use of medical records on dentist performance. Workload does not mediate the influence of the work environment on dentist performance.